2015
DOI: 10.1002/mma.3796
|View full text |Cite
|
Sign up to set email alerts
|

A superconvergence result of the natural convection equations

Abstract: This paper presents a superconvergence result of the stationary natural convection equations. The superconvergence result is obtained by applying a coarse mesh projection for finite element approximation. This projection method is actually a postprocessing procedure that constructs a new approximation based on a high order polynomial on coarse mesh, under some regularity assumption. Finally, numerical experiment is presented for testing, which confirms the theoretic analysis. Copyright © 2015 John Wiley & Sons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In literature review, it appears that heat transfer in natural convection power law non‐Newtonian fluid flow through vertical truncated wavy cone with the Tiwari and Das 22 nanofluid model has not yet been investigated. However, several overlapping studies in one or other way can be found in previous studies 23–41 . In order to fill the gap in literature, the thermally stratified boundary layer CNT–water nanofluid flow suspended by a vertical truncated cone is considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature review, it appears that heat transfer in natural convection power law non‐Newtonian fluid flow through vertical truncated wavy cone with the Tiwari and Das 22 nanofluid model has not yet been investigated. However, several overlapping studies in one or other way can be found in previous studies 23–41 . In order to fill the gap in literature, the thermally stratified boundary layer CNT–water nanofluid flow suspended by a vertical truncated cone is considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, several overlapping studies in one or other way can be found in previous studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] In order to fill the gap in literature, the thermally stratified boundary layer CNT-water nanofluid flow suspended by a vertical truncated cone is considered. Firstly, the system gives a nonsimilar solution; then it converts to a similar solution by using transformation to find its solution.…”
mentioning
confidence: 99%
“…The natural convection model has a long history of use in many fields of production and life, such as in room ventilation, solar collectors, heating general, nuclear reaction systems, fire control, katabatic winds, atmospheric fronts, cooling of electronic equipment, natural ventilation, solar collectors and so on. For more physical explanation, reader is referred to (Sheikholeslami et al , 2019b; Sheikholeslami et al , 2019a; Huang et al , 2016) and the references therein. This paper is concerned with the following stationary natural convection equations (Boland and Layton, 1990): where Ω ⊂ ℝ 2 is assumed that it has a Lipschitz continuous boundary ∂ Ω with a regular open subset Γ.…”
Section: Introductionmentioning
confidence: 99%